HOW DOES WORK ENVIRONMENT INFLUENCE PRODUCTIVITY DURING COVID-19 PANDEMICS? A CASE STUDY IN IPB UNIVERSITY - Ghassani Adisa Nuramalina; Eko Ruddy Cahyadi (Jurnal Aplikasi Bisnis dan Manajemen (JABM), 2021)
Coronavirus was declared as a pandemic by WHO on March 11, 2020. Since that decision, Work From Home (WFH) policy has also begun to be applied to all offices, including educational institutions in Indonesia. IPB, as one of the institutions that also implements the WFH policy, still has to maintain the productivity of its staff although their work environment has been changed. This research aims to analyze the effect of the work environment, both physical and non-physical on the productivity of IPB’s staff in normal work situations and WFH situations. The respondents were obtained by distributing questionnaires online via google form. The data analysis technique used is descriptive analysis, Wilcoxon test, and SEM PLS. The results show that in normal and WFH work situations, physical work environment and non- physical work environment have a positive and significant effect on the productivity of IPB’s staff. It means that the productivity of IPB’s staff can be increased if a good physical and non- physical work environment is available, which suitable for the working condition both during normal and WFH situations. Keywords: educational institution, sem-pls, supporting staff, policy, work from home